FEMALE MASCULINITY IN THE NOVEL "WANASITU ANNI IMRA'AH" BY IHSAN ABDUL QUDDUS BASED ON JOHN BEYNON'S PERSPECTIVE - Muntahana, Nuratul; Basid, Abdul (Annual International Conferences on Language, Literature, and Media; Vol 4 (2022): The 4th Annual International Conference on Language, Literature and MediaDO - 10.18860/aicollim.v4i1.1950, 2022)
Unlike other masculinity studies on man masculinity, this study studies female character masculinity in the novel Wanasitu Anni Imra'ah by Ihsan Abdul Quddus. The purposes of this study are to describe the form of masculinity in female characters and explain the emergence background of masculinity in female characters using John Beynon's Perspective. This is qualitative research. Data collection techniques used are reading technique and note-taking technique. To analyze the data, the researcher used the Miles and Huberman technique which consists of three steps; data reduction, data exposure, and verification. The results of this study are: 1) the form of masculinity includes the desire of being the chairman of the committee, the leader in the family, in command of her child, rising from failure, never feeling weak, wishing to be a man, rejecting the role of a wife, good at playing soccer, good at boxing, proficient in swordplay; 2) the emergence background of masculinity in the Suad character, such as: being active in school activities, family devotion, divorce, escape from destruction, high opinionated and ambition, strong principle, father's hope of having a son, don't want to be a helper for her husband, and unable to refrain herself, her boxer cousin.